New types of damage to forest trees typical of the Mediterranean region - Clauser, F.; GELLINI, R.; Bussotti, F.; Cenni, E.; Bottacci, A. (European Journal of Forest Pathology, 1989)
Since 1984 a new type of damage to the typical tree species growing in the mediterranean area has been observed. The pathological picture includes the typical features of “Waldsterben”. The new symptoms occurring in Pinus pinea, P. pinaster, P. halepensis and Quercus ilex are described.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: crown damage; damage; decline (voyant); foliage reduction